Highly sensitive and integrated VOC sensor based on silicon nanophotonics - Li, Z. Y. (2021)
An integrated volatile organic compounds (VOC) sensor based on silicon photonic ring resonator system is presented in this paper. A thin absorption layer is coated on the silicon surface required to selectively trap the target gas and response as refractive index change. This acts as the main sensing unit, which subsequently affect the resonance peak position. The relative high sensitivity (1.7 pm/ 1000 ppm for acetone), high stability (<1 pm drift) and fast response time (∼20 s) make it a perfect candidate for VOC safety monitoring and warning.